The Chlamydial Type III Secretion Mechanism: Revealing Cracks in a Tough Nut - Betts-Hampikian, Helen J.; Fields, Kenneth (Frontiers in Microbiology, 2010)
Present-day members of the Chlamydiaceae contain parasitic bacteria that have been co-evolving with their eukaryotic hosts over hundreds of millions of years. Likewise, a type III secretion system encoded within all genomes has been refined to complement the unique obligate intracellular niche colonized so successfully by Chlamydia spp. All this adaptation has occurred in the apparent absence of the horizontal gene transfer responsible for creating the wide range of diversity in other Gram-negative, type III-expressing bacteria. The result is a system that is, in many ways, uniquely chlamydial. A critical mass of information has been amassed that sheds significant light on how the chlamydial secretion system functions and contributes to an obligate intracellular lifestyle. Although the overall mechanism is certainly similar to homologous systems, an image has emerged where the chlamydial secretion system is essential for both survival and virulence. Numerous differences, some subtle and some profound, differentiate chlamydial type III secretion from others. Herein, we provide a comprehensive review of the current state of knowledge regarding the Chlamydia type III secretion mechanism. We focus on the aspects that are distinctly chlamydial and comment on how this important system influences chlamydial pathogenesis. Gaining a grasp on this fascinating system has been challenging in the absence of a tractable genetic system. However, the surface of this tough nut has been scored and the future promises to be fruitful and revealing.